2014
DOI: 10.1111/jcpe.12238
|View full text |Cite
|
Sign up to set email alerts
|

The presence, function and regulation of IL‐17 and Th17 cells in periodontitis

Abstract: Periodontitis (PD) is a chronic inflammatory disease characterised by tissue inflammation and destruction of the associated alveolar bone. It is caused by the colonisation of the bacterial plaque biofilm and the resultant host immune responses in the surrounding periodontal tissues. The pro-inflammatory cytokine IL-17, and IL-17 producing CD4+ T cells (also called Th17 cells) have been shown to play an important role in many inflammatory diseases. There is increasing evidence of the presence of IL-17 and Th17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 109 publications
5
120
1
5
Order By: Relevance
“…The actions of cytokines include several effects on immune cells and modulation of inflammatory responses [10,11]. The cytokines are produced by cells in the periodontal tissue as fibroblasts and osteoblasts, and they participate in normal physiological bone turnover and remodeling [11][12][13][14][15][16][17]. Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actions of cytokines include several effects on immune cells and modulation of inflammatory responses [10,11]. The cytokines are produced by cells in the periodontal tissue as fibroblasts and osteoblasts, and they participate in normal physiological bone turnover and remodeling [11][12][13][14][15][16][17]. Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15].…”
Section: Introductionmentioning
confidence: 99%
“…Many characteristics of these cytokines are of interest in orthodontics, since cytokines in the GCF reflect the microenvironment of periodontal tissues, in which orthodontic forces are applied [2,4,15]. Several studies also revealed that cytokines are fundamental in cell signaling in bone [14,18,19] and in mediating mechanically induced bone remodeling (e.g. by orthodontic forces) [1,2,20].…”
Section: Introductionmentioning
confidence: 99%
“…The best examined pathway includes the balance between Th17 cells and Tregs (18). Because PL-MSCs down-regulate IL-17 production by human T cells (Colic et al, unpublished results), it can be postulated that such a mechanism could be responsible for the counterbalanced action of Th17 cells and Tregs in our model.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 91%
“…The presence of specific antibod ies for oral bacteria in patients with periodontitis indicates an involvement of adaptive immune responses [68], of which different T-cell subsets play a detrimental role in the pathogenesis of this inflammatory disease. The T-cell-associated cytokine profile in gingival tissue suggests an engagement of T-helper (Th) 1, Th2, and Th17 cells [69][70][71]. These T-cell subsets are associated with host-derived tissue destruction and bone loss, through, for example, Receptor activator of nuclear factor kappa-B ligand (RANKL) expression.…”
Section: Leukocytesmentioning
confidence: 99%